Inferior alveolar nerve blocks for postoperative pain control after mandibular distraction with osteotomies in a neonate. Issue 6 (10th March 2014) - Krodel, David J.; Belvis, Dawn; Suresh, Santhanam; Polaner, David
Summary We describe the use of inferior alveolar nerve blocks (IANBs) for postoperative pain control for a neonate undergoing mandibular distraction and osteotomies. In this case, bilateral IANBs were effective in keeping low pain scores as assessed on the neonatal infant pain scale (NIPS) and the amount of opioid and adjuvant analgesics used. The blocks were assessed to have lasted approximately 24 h making serial blocks for pain control logistically feasible. Additionally, pain control was improved throughout the period of distractor advancement (approximately 7 days). We propose the routine use of this regional technique for improved pain control after this procedure in neonates and suggest that improved pain control may facilitate earlier extubation in this challenging population.